Study of Human Tacit Knowledge Based on Electroencephalogram Signal Characteristics - Zhang, Tao; Hua, Chengcheng; Chen, Jichi; He, Enqiu; Wang, Hong (Frontiers in Neuroscience, 2021)
Tacit knowledge is the kind of knowledge that is difficult to transfer to another person by means of writing it down or verbalizing it. In a mineral grinding process, the proficiency of the operators depends on the tacit knowledge gained from their experience and training more than a handbook. This paper proposed a method combining the EEG signals and the industrial process to detect the proficiency of the operators in mineral grinding process to reveal the effect of tacit knowledge on the functional cortical connection. The functional brain networks of operators were established based on partial direct coherence and directed transfer function of EEG, and the multi-classifiers were used with the graph-theoretic indexes of the FBNs as input to distinguish the trained operators (Hps) and the non-trained operators (Lps). The results showed that the brain networks of Hps had the better connectivity than that of Lps (p<0.01), and the accuracy of classification was up to 94.2%. Our studies confirm that based on the performance of EEG features and the combination of industrial operational operation and cognitive processes, the proficiency of the operators can be detected.